Plant geography of Chile - Moreira-Munoz, Andres (Plant and Vegetation, 2011)
The first and so far only Plant Geography of Chile was written about 100 years ago, since when many things have changed: plants have been renamed and reclassified; taxonomy and systematics have experienced deep changes as have biology, geography, and biogeography. The time is therefore ripe for a new look at Chile?s plants and their distribution. Focusing on three key issues botany/systematics, geography and biogeographical analysis, this book presents a thoroughly updated synthesis both of Chilean plant geography and of the different approaches to studying it. Because of its range from the neotropics to the temperate sub-Antarctic ? Chile?s flora provides a critical insight into evolutionary patterns, particularly in relation to the distribution along the latitudinal profiles and the global geographical relationships of the country?s genera. The consequences of these relations for the evolution of the Chilean Flora are discussed. This book will provide a valuable resource for both graduate students and researchers in botany, plant taxonomy and systematics, biogeography, evolutionary biology and plant conservation.